2014
DOI: 10.1161/hypertensionaha.113.02564
|View full text |Cite
|
Sign up to set email alerts
|

Fructose Stimulates Na/H Exchange Activity and Sensitizes the Proximal Tubule to Angiotensin II

Abstract: Abstract-The proximal nephron reabsorbs 60% to 70% of the fluid and sodium and most of the filtered bicarbonate via Na/H exchanger 3. Enhanced proximal nephron transport is implicated in hypertension. Our findings show that a fructose-enriched diet causes salt sensitivity. We hypothesized that fructose stimulates luminal Na/H exchange activity and sensitizes the proximal tubule to angiotensin II. Na/H exchange was measured in rat proximal tubules as the rate of intracellular pH (pH i ) recovery in fluorescent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
96
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(103 citation statements)
references
References 40 publications
7
96
0
Order By: Relevance
“…44,45 We recently showed that orally administered fructose augments circulating vasopressin levels (as determined by measuring copeptin, a validated biomarker for vasopressin 46 ) and urinary concentration in dehydrated rats. 47 Fructose also stimulates urinary sodium reabsorption 48 and reduces urea excretion 49 similar to vasopressin.…”
Section: Vasopressin: the Survival Hormonementioning
confidence: 99%
“…44,45 We recently showed that orally administered fructose augments circulating vasopressin levels (as determined by measuring copeptin, a validated biomarker for vasopressin 46 ) and urinary concentration in dehydrated rats. 47 Fructose also stimulates urinary sodium reabsorption 48 and reduces urea excretion 49 similar to vasopressin.…”
Section: Vasopressin: the Survival Hormonementioning
confidence: 99%
“…Excessive fructose intake has been linked to the epidemics of diabetes mellitus 1 , obesity 2 , renal failure 3, 4 , and hypertension 2 . Many previous studies have reported that feeding rats with a high-fructose (HF) diet causes hypertension 2 , whereas Brands et al 3 and Bezerra et al 4 showed that an HF diet alone did not increase blood pressure (BP) in rats, but induced salt-sensitive hypertension in conjunction with a high-salt (HS) diet as assessed by using radiotelemetry 57 . D'Angelo et al also pointed out that previous reports of HF-induced hypertension reflect a heightened response to restraint and thermal stress, leading to an increase in sympathetic output and contributing to the increase in BP, as monitored by using the tail-cuff method 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Stationary micro-infusion of fructose into the proximal tubules of Wistar rats caused a dose-dependent increase in NHE3 activity, and it was demonstrated both in vivo and in vitro that fructose causes phosphorylation and activation of NHE3 via downregulation of a PKA signaling pathway [62]. In separate studies dietary fructose supplementation prior to and during increased dietary salt intake evokes the development of salt-sensitive hypertension in the salt resistant Sprague-Dawley rat [63]. Companion ex vivo studies of isolated and perfused proximal tubules suggest that 1) fructose stimulates NHE3 activity in a PKC-dependent manner and, 2) that Ang-II mediated-stimulation of NHE3 activity is enhanced by fructose [63].…”
Section: Dietary Intake and Renal Sodium Handlingmentioning
confidence: 99%
“…In separate studies dietary fructose supplementation prior to and during increased dietary salt intake evokes the development of salt-sensitive hypertension in the salt resistant Sprague-Dawley rat [63]. Companion ex vivo studies of isolated and perfused proximal tubules suggest that 1) fructose stimulates NHE3 activity in a PKC-dependent manner and, 2) that Ang-II mediated-stimulation of NHE3 activity is enhanced by fructose [63]. Together, these studies suggest that a typical Western diet, which features low potassium intake and high fructose and sodium intake, promotes the prevalence salt-sensitive hypertension by modulating renal sodium transporter activity and expression to drive renal sodium retention (Table 3).…”
Section: Dietary Intake and Renal Sodium Handlingmentioning
confidence: 99%